User And Bandwidth Management Using Mikrotik Hotspot At State Vocational School 5 Waingapu: Manajemen Pengguna dan Bandwidth Menggunakan Hotspot Mikrotik Pada Sekolah Menengah Kejuruan Negeri 5 Waingapu - Hariadi, Fajar; Anamatalu, Deonisius (JOINCS (Journal of Informatics, Network, and Computer Science), 2023)
The use of the internet in schools is very helpful for teachers, staff and students, the internet is an important need for most adult people, they even regard the internet as a basic daily need that must be met, such as at SMK Negeri 5 Waingapu. The use of the internet in schools is very helpful for teachers, staff and students. State Vocational High School 5 Waingapu uses an internet service provider (ISP) sourced from KOMINFO Bakti as internet access with a total bandwidth of 2 Mbps with an average user of 15 clients. The distance to access the internet network on WIFi is 20 meters, but there is still no good management of network usage so that when accessing the internet, many users (clients) often experience interference. One form of utilizing wireless technology is a hotspot. The development method used in this research is to develop a hotspot network at SMK Negeri 5 Waingapu using the Network Development Life Cycle (NDLC) model which is used as the overall development method in developing or designing computer network systems. By implementing bandwidth management using a hotspot router proxy at SMK Negeri 5 Waingapu and testing it using a speedtest before implementation, namely a download speed of 4.55 and an upload speed of 1.09. And after the implementation of bandwidth management for teacher user hotspots, namely for download bandwidth of 0.95 Mbps and upload bandwidth of 0.21 Mbps, then for hotspot user principals download bandwidth is 0.94 Mbps and upload bandwidth is 0.94 Mbps and hotspot user download bandwidth for students is 0.73 Mbps and upload of 0.94 Mbps.